Out of Time - Carl, Franklin; Carter, Alex.; Dean Cain; Eva Mendes; John Billingsley; Robert Baker; Sanaa Lathan; Denzel Washington (USA Metro-Goldwyn-Mayer (MGM), 2003)
Matt Lee Whitlock (Washington), respected chief of police in small Banyan Key, Florida, must solve a vicious double homicide before he himself falls under suspicion. Matt Lee has to stay a few steps ahead of his own police force and everyone he's trusted in order to find out the truth.
A Florida police chief must solve a vicious double homicide before he himself falls under suspicion.
David Collard
Language(s): English, Turkish Subtitle(s): English, Turkish
Keywords: Drama; Thriller; Crime